Audit committee and financial reporting quality: the mediating effect of audit price in Nigeria. (10th February 2021) - Bala, Hussaini; Amran, Noor Afza; Shaari, Hasnah
This study examines the mediating effect of audit price on the link between the audit committee and financial reporting quality. The model was developed based on a complementary hypothesis and employs a panel dataset comprising 440 firm-year observations. We found that a larger audit committee comprising directors and shareholders is more likely to reduce earnings manipulation in the form of artificial smoothing and managers' discretion on earnings. The study also establishes that larger audit committee size is linked to an increase in audit price. Interestingly, we found that an increase in the price of auditing services minimises the likelihood of earnings manipulation. Also the audit price partially and significantly mediates the link between the audit committee and financial reporting quality. This study also informs regulators and policy makers of the importance of audit price in limiting earnings manipulation and boosting audit quality, which, in turn, enhances financial reporting quality.